Behind the use of Code Switching and Code Mixing on Maudy Ayunda’s Youtube Video Content - Juliani Putri, Anita; Dwi Putri Maharani; Yesika Dian Saputri; Teguh Sarosa (ITScience (Information Technology and Science), 2025)
Bilingualism is a linguistic phenomenon characterized by the use of two languages in everyday life. In a bilingual context, communication practices often give rise to the phenomena of code switching and code mixing as language strategies. Code switching is understood as the practice of alternating between languages in discourse, while code mixing entails the incorporation of components from different languages into one utterance without an entire switch of language. A descriptive qualitative method was utilized in this study to analyze the observed phenomena. The research data was obtained from a video podcast by Maudy Ayunda and Jovial da Lopez entitled Dating Tips: 'Jangan Dikit-Dikit Putus